2019
DOI: 10.1111/1440-1703.12072
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses of the biocrust moss Syntrichia caninervis to experimental snow cover manipulations in a temperate desert of central Asia

Abstract: Global warming has given rise to variations in winter weather patterns, including changes in snow cover and soil hydrothermal properties. Biocrust mosses are a major component of desert ecosystems and are relatively sensitive to environmental change, yet the knowledge of possible ecophysiological responses of biocrust mosses to variations in annual snow cover is limited. The aim of this study was to understand how Syntrichia caninervis responds to simulated snow cover alterations in a temperate desert. Ecophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The average annual temperature is 6–10°C with extremes of 40°C or more, the annual cumulative temperature of 3000–5000°C in years ≥10°C, and average relative humidity of 50%-60%, with May through August typically below 45% ( Zhang et al., 2007 ). The basic landscape features of the desert are linear and dendritic longitudinal dunes, and the vegetation is a shrub and small tree communities consisting of Haloxylon persicum , Haloxylon ammodendron , Ephedra przewalskii , Calligonum mongolicum , and other sandy plants ( Zhang, 2020 ). Unlike other desert ecosystems, the Gurbantunggut Desert has a stable snow cover of 15–30 cm in winter, which accounts for 25% of annual precipitation and provides a suitable environment for the development of biological soil crusts in this desert.…”
Section: Methodsmentioning
confidence: 99%
“…The average annual temperature is 6–10°C with extremes of 40°C or more, the annual cumulative temperature of 3000–5000°C in years ≥10°C, and average relative humidity of 50%-60%, with May through August typically below 45% ( Zhang et al., 2007 ). The basic landscape features of the desert are linear and dendritic longitudinal dunes, and the vegetation is a shrub and small tree communities consisting of Haloxylon persicum , Haloxylon ammodendron , Ephedra przewalskii , Calligonum mongolicum , and other sandy plants ( Zhang, 2020 ). Unlike other desert ecosystems, the Gurbantunggut Desert has a stable snow cover of 15–30 cm in winter, which accounts for 25% of annual precipitation and provides a suitable environment for the development of biological soil crusts in this desert.…”
Section: Methodsmentioning
confidence: 99%
“…The study site with a typical temperate continental climate with a mean annual temperature ranging from 5 to 10 °C, and the mean annual precipitation range from 100 to 150 mm. The mean annual potential evaporation reaches 2000 mm, while the relative humidity ranges from 40 to 60% 23 . The most common vascular plants included Haloxylon ammodendron , Erodium oxyrrhynchum , Salsola ruthenica and Calligonum leucocladum ; which are the builders of native vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…Among all types of BSCs, mosses crusts are the most common in the world, Syntrichia caninervis is widely distributed across the drylands of the Northern Hemisphere from the Mojave Desert in the United the States through parts of Europe, to the Gurbantünggüt Desert in China 19 . Till now, there are many studies on tolerance strategy to drought 20 , 21 , and the response of physicochemical properties and spectrally monitoring on environmental change 22 , 23 . However, few studies have looked at the tolerance mechanisms of S. caninervis to Hg toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, snow is a critical source of water for biocrust-forming mosses during the melting period in spring and forms a layer protecting from subfreezing temperatures in winter. For example, in the Gurbantunggut Desert (China), several positive effects of an increase in snowfall have been reported: it can reduce the oxidative, temperature, and desiccation stresses during winter and spring ( Zhang and Zhang, 2020 ), and the greater water availability it provides when it melts enables higher growth from spring to early autumn ( Zhao et al , 2016 ). Hui et al (2018) also observed a positive effect of a moderate increase in snow depth on the chlorophyll content and photochemical efficiency after an individual snow event.…”
Section: Adaptations Of Biocrust-forming Mosses To Dryland Environmen...mentioning
confidence: 99%